THE ASIA PACIFIC BIOETHICS PROGRAM OF THE UNESCO CHAIR IN BIOETHICSCAN RESEARCH IN DEVELOPING COUNTRIES BE BOTH ETHICAL AND BENEFICIAL TO LOGAL COMMUNITY ? - Theong H. Low (Faculty of Medicine, Universitas Andalas, 2014)
Abstractln 2005 at the 33rd Session of General Conference at UNESCO, it adapted the Universaldeclaration on Bioethics and Human Rights. Declaration article 1.1 outlines the principals thatrespond to ethical issue related to medicine, life sciences and associated technologies as appliedto human beings. Thus the international standards for Bioethics are grounded in a language ofrights -to safe guard human dignity and human rights. UNESCO made ethics of Science andtechnology one of its 5 priority areas. lt is charged with promoting the education of ethical issuesof Science and Technology. The UNESCO Program in this area aims to strengthen lhe ethicallink between scientific advancement that is taking place and the Cultural, Legal, Philosophicaland religious context in which it occurs.The disparity of health amongst the world's communitiesis largely determined by the wealth of the countries. Developed countries have access to cleanwaters, vaccines and new medical technologies whereas developing countries do not.Researches in these countries are also funded by the wealthy countries and we will need toprotect these countries from exploitation by those with the means in the name of clinicalresearch.Hence, we have to discuss the necessary conditions for models allowing lnstitutionalReview Boards to grani exceptions in low income countries to circumvent the need for